Online Training Methods in Improving Early Childhood Teacher Pedagogic Competence - Maryani, Kristiana; Yufiarti, Yufiarti; Yetti, Elindra (Universitas Negeri Semarang, 2021)
This study aims to determine how the process of online training methods to improve early childhood pedagogical competence of teachers, early childhood teachers pedagogical competence results after following the online training methods as well as the responses obtained by the participants after attending online training methods. Pedagogic competence of teachers is the ability to manage learning, which includes planning, implementation, and evaluation of learning outcomes of students. Pedagogical competence developed through training in collaboration between knowledge and practice so easily applied in learning. One method of training was initiated by the government is an online training method implemented in basic training. This study uses qualitative research methods with the data source 24 early childhood teachers who are in the district of Bogor. Data collection technique used interview, observation and field notes with the data analysis using data reduction, data presentation, and verification of data. The results of this study mention the pedagogical competence of the 24 teachers who have been following the online training methods 21 people are at a high category and three are in the moderate category. Similarly with the results of interviews at every teacher stated that the results were very good and positive after following the online training to improve the quality of learning in the classroom.